Perancangan Touchless Hand Washer Sistem Pijakan Kaki untuk Pencegahan Penyebaran COVID-19 - Sulaiman Ali; Syurkarni Ali; Herdi Susanto; Rita Hartati; Zahir Raditya (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2020)
The spread of the Coronavirus Disease (COVID-19) outbreak in all parts of the world is increasing, including in Indonesia, a virus that is easily transmitted and spreads through close contact and droplets by touching hands with other people or with objects that have been exposed to COVID-19, one of the reasons for this, reventing the spread of COVID 19 by washing hands frequently with soap. Hand washing tools have been developed, generally still using direct touch to the water tap and soap dish, the Touchless Hand Washer (THW) touchless hand washing tool is specially designed and manufactured in accordance with the COVID-19 pandemic conditions without touching with hands directly on the water tap and a soap holder with a footrest system, making it more practical, hygienic and not directly contaminated with previous Touchless Hand Washer users which could cause COVID-19 transmission from previous users. Touchless Hand Washer (THW) is designed with a pyramid-shaped frame that will support the water toren that does not harm or the water toren falls for Touchless Hand Washe users, with a THW tool height of 120 cm, top width 70 x 70 cm and bottom width of 90 x 90 cm. Keywords—Hand-washing tool, COVID-19, washing hands, touchless hand washer